Corporate Social Responsibility dan Cost of Capital - Rahmat Setiawan; Savira Rizma Yunita (Jurnal Akuntansi, 2023)
This study aims to see how disclosure of corporate social responsibility (CSR) impacts the cost of capital (COC). This study uses 260 observations of non-financial companies listed on the IDX from 2016 to 2018. The technical analysis in this study is multiple linear regression analysis. The results show that corporate social responsibility has a negative effect on the cost of equity and cost of debt. Keywords: Corporate Social Responsibility, Cost of Debt, and Cost of Capital